SOSIALISASI PENTINGNYA BABY GYM UNTUK MEMAKSIMALKAN PERKEMBANGAN MOTORIK KASAR PADA BAYI USIA 3-6 BULAN DI DESA SUKOREJO KECAMATAN NGASEM KABUPATEN KEDIRI - Putri Wahyu Wigati; Dhita Kris Prasetyanti; Sutrisni; Halimatus Saidah; Galuh Pradian Yanuaringsih (Universitas Kadiri, 2026)
Infant development can be broken down into four aspects: gross motor skills, fine motor skills, personal-social skills, and language. Stimulation in the form of exercise is one way to safeguard infant growth and motor development. Potential problems, if a child is not stimulated, include delayed motor development or a suboptimal motor development process. Given the numerous negative impacts, increased vigilance is needed for potential hazards. Social approaches in the form of baby gym or infant gymnastics need to be optimized to enhance growth optimization efforts, one of which is through outreach using teaching methods on infant gymnastics. This outreach activity has been proven to improve infant growth at Sukorejo Village, Ngasem Community Health Center, Kediri Regency. However, ongoing support is needed so that mothers can deepen their infant's motor growth and development.